InP/ZnS quantum dot photoluminescence modulation via in situ H2S interface engineering. Issue 4 (15th February 2023) - Fan, Xiang-Bing; Shin, Dong-Wook; Lee, Sanghyo; Ye, Junzhi; Yu, Shan; Morgan, David J.; Arbab, Adrees; Yang, Jiajie; Jo, Jeong-Wan; Kim, Yoonwoo; Jung, Sung-Min; Davies, Philip R.; et al.
Abstract : High photoluminescent InP/ZnS QDs synthesis by in situ H2 S interface engineering. Abstract : InP quantum dots (QDs) are attracting significant interest as a potentially less toxic alternative to Cd-based QDs in many research areas. Although InP-based core/shell QDs with excellent photoluminescence properties have been reported so far, sophisticated interface treatment to eliminate defects is often necessary. Herein, using aminophosphine as a seeding source of phosphorus, we find that H2 S can be efficiently generated from the reaction between a thiol and an alkylamine at high temperatures. Apart from general comprehension that H2 S acts as a S precursor, it is revealed that with core etching by H2 S, the interface between InP and ZnS can be reconstructed with S 2− incorporation. Such a transition layer can reduce inherent defects at the interface, resulting in significant photoluminescence (PL) enhancement. Meanwhile, the size of the InP core could be further controlled by H2 S etching, which offers a feasible process to obtain wide band gap InP-based QDs with blue emission.